Respuesta :
Answer:
[tex]-\frac{11}{12}[/tex]
Step-by-step explanation:
[tex](\frac{5}{8}+ \frac{3}{4} )/(-\frac{2}{3} -\frac{5}{6})[/tex]
8 = 2 × 2 × 2
4 = 2 × 2
LCM = 2 × 2 × 2
LCM = 8
3 = 3 × 1
6 = 2 × 3
LCM = 2 × 3 × 1
LCM = 6
[tex](\frac{5}{8}+ \frac{2(3)}{2(4)} )/(-\frac{2(2)}{2(3)} -\frac{5}{6})[/tex]
[tex](\frac{5}{8}+ \frac{6}{8} )/(-\frac{4}{6} -\frac{5}{6})[/tex]
[tex]\frac{11}{8}/(-\frac{4}{6} -\frac{5}{6})[/tex]
[tex]\frac{11}{8}/-\frac{9}{6}[/tex]
[tex]\frac{11}{8}(-\frac{6}{9})[/tex]
[tex]-\frac{66}{72}[/tex]
66 = 2 × 3 × 11
72 = 2 × 2 × 2 × 3 × 3
GCF = 2 × 3
GCF = 6
[tex]-\frac{66/6}{72/6}[/tex]
[tex]-\frac{11}{12}[/tex]